PRINCIPLE OF SUBSIDIARITY ECONOMIC STATE OF THE POLITIC CONSTITUTION IN PERU - Rodríguez Cairo, Vladimir (2013)
The research paper entitled “Principle of subsidiarity economic state of the politic Constitution in Peru” seeks to answer the following question: What is the scope of the constitutional principle of state economic subsidiarity? In this regard, it should be noted that this study is an explanatory and documentary. Similarly, the research method used is analytical and inductive. He turned to secondary sources and how technical the document review. In this perspective, for a better understanding of the subject, the content of this document is structured in three parts: the first sets out the background, the second raises the foundation of economic subsidiarity principle and the third state covers matters relating the limits of state power and state functions. Then, we present our conclusions. Finally, the literature discloses.